Single-Cell RNA-Seq Steps Up to the Growth Plate. Issue 7 (July 2016) - Morris, Samantha A.
Abstract : Single-cell RNA sequencing (RNA-seq) technology is hitting its stride and is beginning to be widely adopted. One of the major challenges faced by this rapidly growing field lies in data analysis. Li et al. now present Sinova, a single-cell analytical platform offering temporal, spatial, and regulatory reconstruction of developmental processes.